cTAGE: a cutaneous T cell lymphoma associated antigen family with tumor-specific splicing - Usener, Dirk; Schadendorf, Dirk; Koch, Joachim; Dübel, Stefan; Eichmüller, Stefan B. (The journal of investigative dermatology, 2015)
cTAGE-1 is a cutaneous-T-cell-lymphoma-specific tumor antigen recently identified by serologic identification of antigens by recombinant expression cloning. This study was aimed at identifying and characterizing related genes. Rapid amplification of cDNA ends and DNA screening led to five new members of the cTAGE gene family belonging to four different genes, two of which were differentially spliced (cTAGE-1/2 and cTAGE-5). Expression analysis using reverse transcription polymerase chain reaction revealed that cTAGE-1, cTAGE-1B, and cTAGE-5A expression was restricted to testis and tumor tissues, whereas the other cTAGE members were found in two to eight other normal tissues (of 27 tissues tested). Tumor-specific protein expression of cTAGE-5 was confirmed by Western blotting. Sero-reactivity against cTAGE-1, cTAGE-4, cTAGE-5A, and cTAGE-5B was found only in tumor patients (cutaneous T cell lymphoma and melanoma). The immunogenic epitope of cTAGE-1 was determined by using epitope mapping and sera of two cutaneous T cell lymphoma patients. Moreover, cTAGE-1, cTAGE-4, cTAGE-5A, and cTAGE-5B could be detected in most types of tumor tissues and cell lines at variable frequencies, including those of cutaneous T cell lymphoma, melanoma, head and neck squamous cell carcinoma, breast carcinoma, and colon carcinoma. We conclude that cTAGE-1 and cTAGE-5 are new cancer germline antigens and that tumor-specific splicing of cTAGE genes may lead to further candidate proteins for specific immunotherapy of cutaneous T cell lymphoma and other malignancies.